Harmonization of Dayak Customary Law and Islamic Values in Handling Cases of Pregnant Marriage in Sajingan Besar on the Indonesia-Malaysia Border, West Kalimantan - Asman (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
This study aims to explore the harmonization between Islamic values and Dayak customary law in addressing premarital pregnancy marriage cases in Sajingan Besar District, located on the Indonesia-Malaysia border in West Kalimantan. Premarital pregnancy marriage, or marriage triggered by out-of-wedlock pregnancy, is a complex and sensitive social phenomenon, especially in multicultural areas where religious and customary norms coexist strongly. A qualitative approach was employed through in-depth interviews, participatory observation, and document analysis. The findings reveal that although there are normative differences between Islam and Dayak customary law, both aim to uphold family honor, social stability, and the child's well-being. In practice, the Sajingan Besar community resolves such cases through customary deliberation mechanisms grounded in justice, responsibility, and the involvement of religious and traditional leaders. This harmonization is achieved through open dialogue and flexibility in interpreting both customary law and Islamic principles. The study demonstrates that integrating religious and local customary values can serve as an effective solution in managing moral and culturally-based social conflicts in border regions.